Struggle for urban citizenship in South Africa: Agency and politics in the Enkanini upgrading project, Stellenbosch - Zibagwe, Scelo (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.